Aronia berry (Aronia mitschurinii 'Viking') inhibits colitis in mice and inhibits T cell tumour necrosis factor-α secretion. (May 2018) - Martin, Derek A.; Smyth, Joan A.; Liu, Zhenhua; Bolling, Bradley W.
Highlights: Aronia berry supplementation increased colonic IL-10 secretion in healthy mice. Aronia berry protected against wasting associated with colitis. Aronia extracts and polyphenols inhibited T cell TNF-α in vitro . Certain polyphenol catabolites were more potent TNF-α inhibitors than anthocyanins. Abstract: Aronia berries are rich in polyphenols with anti-inflammatory activity. We hypothesized that aronia berry consumption modulates intestinal immune function and T cells. The aims of the present work were to assess the immunomodulatory potential of 'Viking' aronia berry (black chokeberry, Aronia mitschurinii ) in vivo and to determine the extent aronia berry polyphenols or known microbial polyphenol catabolites inhibit T cell tumour necrosis factor (TNF)-α in vitro . Aronia berry consumption increased colonic IL-10 secretion in healthy mice, but did not inhibit ex vivo cytokine secretion of lipopolysaccharide-stimulated spleen and colon tissue. Aronia berry consumption inhibited wasting associated with T cell adoptive transfer and dextran sulphate sodium induced colitis. Aronia extracts, neutral phenols fraction, and the polyphenol catabolites 3, 4-dihydroxyphenylacetic acid and 3, 4-dihydroxyphenylpropionic acid inhibited TNF-α production in Jurkat T cells. Therefore, T cells and microbial catabolism partly mediate the anti-inflammatory effects of aronia consumption in the colon.